Granulomatous dermatitis following measles, mumps, and rubella vaccination. Issue 5 (15th July 2021) - Samaran, Quentin; Clark, Evangéline; Secco, Léo‐Paul; Poujade, Laura; Schwob, Emilie; Bessis, Didier; Raison‐Peyron, Nadia
Abstract: Granulomatous dermatitis following the administration of various vaccines has previously been reported. However, cases of cutaneous granulomatosis following the measles, mumps, and rubella (MMR) vaccine have not yet been reported. We report the case of a 3‐year‐old boy with a granuloma annulare‐like reaction following MMR vaccination.